Reminiscence Therapy as a Potential Method to Improve Psychological Health and Quality of Life in Elderly Hepatocellular Carcinoma Patients: A Randomized, Controlled Trial - Li, Teng; Li, Bin; Tan, Lu; Lv, Bo (Frontiers in Surgery, 2022)
Background Reminiscence therapy mitigates psychological issues and improves the quality of life of cancer survivors. However, its role in elderly patients with hepatocellular carcinoma (HCC) is unclear. Thus, we aimed to detect the effect of reminiscence therapy on anxiety, depression, and the quality of life of elderly patients with HCC. Methods In total, 106 elderly patients with HCC after resection were randomized in a 1:1 ratio to the reminiscence therapy group (N = 54) and control care group (N = 52) and then received intervention for 12 months. Anxiety and depression were evaluated by the Hospital Anxiety and Depression Scale (HADS) at baseline [Month (M) 0], 3 months (M3), 6 months (M6), 9 months (M9), and 12 months (M12). Meanwhile, quality of life was assessed using the European Organization for Research and Treatment of Cancer quality of life Questionnaire—Core 30 (QLQ-C30) at M0, M6, and M12. Results The HADS for anxiety score at M9 (6.8 ± 2.3 vs. 7.8 ± 2.4, P = 0.039) and M12 (6.6 ± 2.4 vs. 7.8 ± 2.6, P = 0.013) and the anxiety proportion at M12 (27.8% vs. 46.2%, P = 0.050) were reduced in the reminiscence therapy group compared with those in the control care group. Moreover, the HADS for depression score declined at M9 (6.6 ± 2.0 vs. 7.5 ± 2.2, P = 0.025) and M12 (6.3 ± 2.3 vs. 7.7 ± 2.6, P = 0.005), but the proportion of those with depression was not different at each visit (P > 0.05) in the reminiscence therapy group compared with that of the control care group. In addition, the QLQ-C30 global health status score increased at M6 (71.3 ± 12.8 vs. 66.3 ± 12.9, P = 0.048) and M12 (74.5 ± 12.9 vs. 68.2 ± 13.3, P = 0.014) in the reminiscence therapy group compared to that in the control care group. Conclusion Reminiscence therapy effectively mitigates anxiety and depression and improves the quality of life of elderly patients with HCC.